Kinetic of liquid-phase reactions catalyzed by acidic resins: The formation of peracetic acid for vegetable oil epoxidation - Musante, R.L. (2000)
A heterogeneous kinetic model which takes into account the complete physicochemical interaction of reactive species in a polar liquid phase with an ion-exchange resin acting both as selective sorbent and heterogeneous catalyst has been employed to analyze the peracetic acid synthesis from acetic acid and hydrogen peroxide in an aqueous solution. Model parameters were estimated using uncoupled data from phase equilibria, polymer sorption, chemical equilibrium and reaction kinetics. Activities rather than molar concentrations in the polymer phase and specific (dry weight of catalyst basis) rather than volume-based expressions were found to give the best constitutive equations for the heterogeneous reaction rate.